Pelaksanaan asuhan gizi dengan pendekatan terapi gizi medis (TGM) berpengaruh terhadap asupan gizi pasien di RSUD Kota Bekasi - Ika Yuliati C; I Made Alit Gunawan; R Dwi Budinigsari (Jurnal Gizi Klinik Indonesia, 2008)
Background: Medical nutrition therapy (MNT) is one of nutrition care models which focuses on integrated patient management involving active participation of doctors, nutritionists, nurses, and other professions within nutrition care team. An indicator of success in nutrition intervention is nutrition intake. Bekasi Municipal Hospital has not implemented integrated nutrition care within a team. The result of monitoring and evaluation during the first quarter of 2006 showed that average patient nutrition intake was only 65-70% (inadequate).Objective: To identify the influence of nutrition care implementation using MNT approach to nutrition intake and length of stay at Bekasi Municipal Hospital.Method: The study was quaci-experimental which used static-group comparison. Samples were patients hospitalized at internal medicine ward of class VIP, 1, 2, and 3. Data obtained consisted of conventional nutrition care and MNT, data of nutrition intake using Comstock visual and 24 hour recall methods. T-test and Mann Whitney statistical test were used to analyze the influence of types of nutrition care to nutrition intake.Results: Average percentage of total nutrition intake of hospital food and outside hospital food sample with MNT nutrition care was better than conventional nutrition care. Total nutrition intake was 91.71% for energy, 92.12% for protein, 111.83% for fat, and 85.41% for carbohydrate. The result was significant for energy intake (p<0.05). Nutrition intake of sample hospital was 86.08% for energy, 88.91% for protein, 108.55% for fat, and 78.91% for carbohydrate. Nutrition intake of outside hospital was 21.94% for energy, 13.77% for protein, 12.22% for fat, and 35.43% for carbohydrate. They were not significant statistically.Conclusion: There was difference in nutrition intake between samples with MNT and conventional nutrition care. Nutrition intake of samples with MNT was better than conventional nutrition care and statistically significant (p<0.05).